The Dynamic Identity: Analysis Of Gender Identity In Breakfast On Pluto By Patrick Mccabe - Ayuningtyas, Paramita (Lingua Cultura, 2011)
Article focused on gender identity in Breakfast on Pluto by Patrick McCabe. By using StuartÂ Hallâ€™s concept of identity, the analysis showed that gender identity had the potential to beÂ deconstructed, as shown by the identity transformation done by Patrick Braden. Positioning by otherÂ people and his own body happened to be barriers for his identity transformation. However, thoseÂ barriers basically could not stop Patrickâ€™s transformation to be a woman. Patrick had its ownÂ strategies in changing his gender identity, which were gender deconstruction, body decoration, andÂ language. It can be concluded that Breakfast on Pluto offers a discourse of identity that is dynamic.Â Identity is a becoming process that will happen endlessly in humanâ€™s life.